The impact of losses on income tax revenue and implicit tax rates of different income sources: evidence from microsimulation using tax statistics for Germany - Stefan Bach; Hermann Buslei (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In order to calculate the burden of a comprehensive and progressive income tax falling on a certain income source, an apportionment scheme for the entire tax burden has to be chosen. This raises the question of how to deal with losses, which is relevant for Germany in view of the heavy losses from renting. Using micro data from tax statistics we analyze the income tax shares of functional income sources for three apportionment schemes. The choice of the apportionment scheme markedly affects the tax shares of income sources and the implicit tax rates, in particular those of capital income.
Keywords: H24; H25; D33; 330; Income and business income taxation; implicit tax rates by income sources; Einkommensteuer; Körperschaftsteuer; Steuerbelastung; Funktionelle Einkommensverteilung; Verlust; Steuerliche Zurechnung; Steuerbegünstigung; Steuertarif; Mikrosimulation; Steuerwirkung; Deutschland